Evaluation of Patients with Cleft Lip and Palate in Southeastern Anatolian Region - Merve Göymen; Yasin Akbulut; Oral Sökücü (Galenos Yayinevi, 2016)
Objective:Our study included patients with cleft lip and palate who applied to Gaziantep University Dentistry Faculty Orthodontics Department between 2010 and 2014. The aim of this study was to reveal the characteristics of these patients with demographic values.Methods:In total, 118 patients were included in this study. The patients were pursued by phone calls, and the study was conducted with only 64 patients. The demographic map was created with a statistical expert as a questionnaire.Results:It was thought that the reason for not being able to include the remaining 54 patients was a change in phone number, designation, or others. One patient who was to be interviewed died because of heart failure. The results revealed that the place of birth of 18.75% patients was a metropolitan region that of 54.68% was a province, that of 21.87% was a district, and that of 4.69% was a village. The majority of patients (93.25%) had a low family income level. The average number of children was 3.28, and readership was 1.47. The rate of working mothers was 1.56%.Conclusion:It was concluded that the cleft lip and palate patient group had lower economic and sociocultural levels. For this purpose, raising awareness of parents and providing financial support to families are required because of the long-term treatment process. It was thought that the long-term treatment process of these patients in a single-unit authority with the guidance of universities would be appropriate for better patient follow-up and inventory. Otherwise, as seen in this study, contact cannot be established after a while and some problems can arise with regard to follow-up. Lack of communication can lead to the formation of more difficult patients with growth and development.